2001
DOI: 10.1038/ncb1001-918
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular control of cell size

Abstract: Both cell growth (cell mass increase) and progression through the cell division cycle are required for sustained cell proliferation. Proliferating cells in culture tend to double in mass before each division, but it is not known how growth and division rates are co-ordinated to ensure that cell size is maintained. The prevailing view is that coordination is achieved because cell growth is rate-limiting for cell-cycle progression. Here, we challenge this view. We have investigated the relationship between cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 20 publications
7
107
2
1
Order By: Relevance
“…In addition, increased cell size might be due to alterations in external signals that dictate growth rates independently of cell cycle progression. It has previously been shown in cell culture systems that growth factor stimulation can lead to cell growth (volume increase), whereas cell cycle progression is blocked (Conlon et al, 2001;Dolznig et al, 2004). A scenario like this might explain the results obtained in our chimerae analyses, where ubc9.1 morphant chondrocytes showed a less pronounced size phenotype when exposed to a wild-type environment.…”
Section: Loss Of Ubc9 Leads To Compromised Mitosis and Cellular Overgsupporting
confidence: 76%
“…In addition, increased cell size might be due to alterations in external signals that dictate growth rates independently of cell cycle progression. It has previously been shown in cell culture systems that growth factor stimulation can lead to cell growth (volume increase), whereas cell cycle progression is blocked (Conlon et al, 2001;Dolznig et al, 2004). A scenario like this might explain the results obtained in our chimerae analyses, where ubc9.1 morphant chondrocytes showed a less pronounced size phenotype when exposed to a wild-type environment.…”
Section: Loss Of Ubc9 Leads To Compromised Mitosis and Cellular Overgsupporting
confidence: 76%
“…Rather, cell size is dynamic and responsive to the extracellular milieu. Indeed, budding yeast grown on poor carbon sources proliferate at reduced cell size (Flick et al, 1998), and rat Schwann cells divide at a size that varies depending on the concentration of extracellular growth factors in the media (Conlon et al, 2001). It is intriguing that the same set of mTOR-dependent downstream effectors that regulate cell growth and cell size, S6K1, 4E-BP1, and eIF4E, also regulate the rate of cell cycle progression: When quiescent U2OS cells are stimulated with serum to enter G 1 phase from G 0 , overexpression of S6K1 and eIF4E accelerates S phase entry, while reduced expression of S6K1 with RNAi or overexpression of a dominant mutant of 4E-BP1 inhibits the rate of S phase entry (Fingar et al, 2004).…”
Section: Rheb An Activator Of Tor That Is Inhibited By Tsc2mentioning
confidence: 99%
“…In an attempt to examine how cell growth and cell division are coordinated in order to keep a constant cell size, Conlon et al [161] examined cell growth and cell division after treatment of rat Schwann cells with glial growth factor (GGF). They found that GGF can stimulate cell cycle progression without promoting cell growth, further confirming studies in yeast and Drosophila that proliferation can not drive cell growth.…”
Section: Interaction Between Cell Growth and Cell Division In Cell Anmentioning
confidence: 99%